A New Method to Reduce Harmonic Magnitude Based on Simultaneous Determination of Maximum Voltage and Current Harmonic Contribution in Interconnected Networks. Issue 8 (9th May 2019) - Momenpour Akerdi, Javad; Torabian Esfahani, Mehdi; Vahidi, Behrooz
Abstract: The issue of power quality (PQ) as an important and necessary concern has been raised in recent years in power systems due to increased polluting and sensitivity loads in the area of power quality phenomena. In this article, a new method is proposed for simultaneous determination of the harmonic contribution of harmonic sources to reduce voltage and current harmonic amplitude in interconnected networks. The major innovation of this article is that, unlike most articles that determine the harmonic contribution solely between the customer and the network, it determines the harmonic contribution in a more comprehensive manner in interconnected networks which include several harmonic loads in different locations. The method presented in this article enjoys the ability to simultaneously do the harmonic contribution of voltage and current with no need to use the results of one for another. In this article, the defects of using the "vector projection" method are presented to solve the above problem; so, a method is proposed based on reducing the amplitude of the harmonic voltage and current due to the reduction of the harmonic amplitude and shifting the phase of each harmonic source. In practical application, the proposed method could be used to determine the maximum potential of each source in reducing the desired harmonic amplitude of the voltage or current, as the harmonic source is conducted more to determined amplitude and phase, more reduction in harmonic amplitude could be observed. Both the proposed method and the "vector projection" method are evaluated in IEEE 6-BUS and IEEE 14-BUS networks using Digsilent and Matlab Software in a specific harmonic frequency. Simulation results show that using the proposed method provides more tangible results to correctly identify the harmonic source which generates the most reduction harmonic voltage or current in the specified bus or line of the network.